The Influence of Individual Factors on Implementation of Green Human Resource Management in The Textile and Apparel Industry - Patrisia Putri Pramadani; Gia Rizky (Jurnal Manajemen dan Profesional, 2026)
The purpose of this research is to examine the influence of employee environmental awareness, green competencies, personality and motivation on the implementation of green human resource management in the textile and apparel industry in Daerah Istimewa Yogyakarta. This research method used a quantitative approach with 95 respondents, which were analysed using logistic regression. The results of the study indicate that all variables simultaneously influence the implementation of GHRM. Partially, employee environmental awareness, green competencies and motivation have a positive and significant effect on the implementation of GHRM, while personality has a negative and significant effect on the implementation of GHRM. This study can be a basis for companies in considering individual factors in the implementation of GHRM. This study is limited to the textile and apparel industry in DIY, therefore, the findings cannot be broadly generalized.